Alih Media Arsip sebagai Pemeliharaan Nilai Evidence: Studi Kasus Arsip Pengadaan Barang dan Jasa di Puslatbang PKASN LAN Tahun 2024 - Zakaria, Muhammad Aldodo; Sagita, Novie Indrawati; Ismail, Febriadi (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
To maintain the unity of information on goods and services procurement records, the media transfer is a necessary step. However, the implementation of media transfer at Puslatbang PKASN LAN still faces various obstacles at several stages. This research aims to analyze and explain each stage of media transfer of goods and services procurement records in order to maintain the value of records evidence. The approach used is Wang and Chen's media transfer theory, which includes: 1) preliminary procedure, 2) digital file establishment, 3) quality inspection, and 4) post-processing. This research uses a descriptive qualitative method with data collection techniques through direct observation, structured interviews, and documentation. The results show that the preliminary procedure stage has included the preparation of an archive list and preparation of tools, but its implementation still depends on the completion of the procurement process. At the digital file establishment stage, scanning using the ALDO AS 2000 Portable Scanner is inconsistent in resolution, which has an impact on the quality of the resulting digital records. The quality inspection stage has been carried out through checking the quality and quantity of the records, this aims to keep the archive information intact in evidence preservation activities. In the post-processing stage, authentication, minutes, and record storage are carried out, but the authentication of records resulting from media transfer has not been optimized due to limited human resources. This affects the legality of digital records when used. The findings show that although media transfer has been implemented, there are still technical and administrative obstacles that can affect the archive's evidence value. The implications of this research emphasize the need to improve technical standards and policies related to the authentication of digital records to ensure the validity and legality of the records resulting from media transfer in the long term.